A comparative study of teaching anatomy using cadavers, prosected wet specimens and simulated plastic models among Malaysian undergraduates - Aung, Htar Htar; Tin, Myo Han (2012)
It is a challenge that the dissecting room still has a place in teaching gross anatomy. Understanding the students’ perceptions and experiences of learning anatomy is important to get sound knowledge of the human body. This study was conducted to assess which teaching aid would facilitate students’ understanding of the human body in order to get a more evidence – based approach to clinical anatomy. A cross – sectional comparative study was carried out among 741 medical and dental students of International Islamic University Malaysia (IIUM), Universiti Teknologi MARA (UiTM), University Sabah Malaysia (USM) and University Malaysia Sarawak (UNIMAS). A pre-tested, semi-structured, self administrated questionnaire which includes open–ended questions was distributed to collect the data on handability, understanding, information, application and preference. The data was analysed using chi-square test at “α“ 0.05 (SPSS version 17). The students from IIUM, UiTM, USM and UNIMAS scored the highest preference for plastic models on handability and application in examination (OSPE). It was statistically significant (p<0.05). In terms of understanding and information, the students of IIUM, UiTM and USM also scored highest on plastic models but UNIMAS chose the prosected wet specimens. The intra-university variation on favourable teaching aid was statistically significant (p<0.05) in IIUM and UiTM but it was not significant (p>0.05) in USM (information and application in OSPE) and UNIMAS (understanding and information). The overall preference for students of IIUM and UiTM was the plastic models (85.8% and 44.1% respectively) while for UNIMAS the prosected wet specimens (90.7%) followed by plastic models (87.8%). USM students mostly preferred the cadavers (51.9%) followed by plastic models (50%). These inter-universities differences were statistically significant (p<0.05). This study suggests that the plastic model can fit very well into the structure of modern medical training and therefore improve the teaching of anatomy in surgical specialities.